The Utilization of Anthocyanin Extract from Parijoto (Medinilla speciosa) as a Sensitizer in Dye-Sensitized Solar Cells (DSSC) - Berghuis, Nila Tanyela; Perangin, Menawari Perangin; Tandawuya, Richard Reynchak (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2024)
The research on the Utilization of Anthocyanin Extract from Parijoto (Medinilla speciosa) as a Sensitizers in Dye Sensitized Solar Cell (DSSC) aims to identify the presence of anthocyanin compounds in parijoto fruit and determine how much power can be generated from anthocyanin compounds as sensitizers in DSSC using variations of ethanol, methanol, ethanol-citric acid (50:50), methanol-citric acid (50:50) solvents through the maceration method for 48 hours. The highest yield was the methanol-citric acid extract from the fruit, which was 16.35%. Positive results in the identification of anthocyanin compounds that were dripped with NaOH showed a color change from red to green-blue and when dripped with HCl there was no color change. The results of the functional group characterization of the fruit ethanol extract through FTIR (Fourier Transform Infrared) analysis showed the presence of -OH groups, -C=C aromatic and -CO alcohol at a wave number of 3293 cm-1, 1644 cm-1, and 1019 cm-1, while from the GCMS (Gas Chromatography Mass Spectrometry) analysis in the fruit ethanol extract there was a cyanidin structural framework at a retention time of 12.24 minutes with a value (m/z) of 243, and an area% of 1.09%. The power measurement on the fruit ethanol extract was 0.1516 mW and on the fruit ethanol-citric acid extract was 0.023 mW. The power generated indicates that the parijoto fruit extract has the potential as a sensitizer in the Dye-Sensitized Solar Cell (DSSC) application.